Synergetic approach to achieve enhanced lithium ion storage performance in ternary phased SnO2–Fe2O3/rGO composite nanostructures - Zhu, Jixin (2012)
We report here a study on the Li ion storage performance of binary phased SnO2/rGO and ternary phased SnO2–Fe2O3/rGO composite nanostructures. The SnO2/rGO and SnO2–Fe2O3/rGO were prepared by a facile wet-chemical approach. The Li storage performances of these samples were closely related to the weight ratio of SnO2 : rGO or SnO2 : Fe2O3 : rGO. It was found that ternary SnO2–Fe2O3/rGO composite nanostructures (e.g. with a weight ratio of SnO2 : Fe2O3 : rGO = 11 : 1 : 13) showed significant enhancement of the specific capacities and cyclabilities as compared to that of SnO2/rGO samples. For example, the SnO2–Fe2O3/rGO electrode depicted a specific capacity of 958 mA h g ^-1 at a current density of 395 mA g ^-1 (0.5 C) during the 100th cycle. Such Li storage performances of the SnO2–Fe2O3/rGO electrodes, especially at high current densities (e.g. 530 mA h g ^- 1 at 5 C rate), were also much better than those reported for either SnO2-based or Fe2O3-based electrodes. Such a synergetic effect in the SnO2/Fe2O3/rGO composite nanostructures is promising for the development of advanced electrode materials for rechargeable Li-ion batteries.